2021
DOI: 10.1177/15280837211012590
|View full text |Cite
|
Sign up to set email alerts
|

Ecofriendly development of electrospun antibacterial membranes loaded with silver nanoparticles

Abstract: Functional polymeric membranes with antibacterial properties have gained significant importance in many applications. Silver NPs offer advantage over other materials for their effective antibacterial properties and being safer for humans at low concentrations. The synthesis of silver NPs may not always be environmental friendly and their incorporation in the polymer membranes is usually a multistep process. In this study, PVDF/PVP/AgNPs electrospun membranes were developed in a single step process where silver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…Mixtures of existing solvents, such as FA and AA with chloroform, acetone, N, N-dimethylformamide, dichloromethane, or even hexafluoro-2-propanol, have been used until now for nano- or micro-fibrous mats preparation by electrospinning [ 57 , 58 , 63 ]. Virgin polyamide has already been electrospun for many applications, such as water or air filtration, composites with antioxidant activity, or improved mechanical properties [ 53 , 54 , 55 , 56 ]. HFIP is an acidic alcohol, and due to its strong hydrogen bonding properties, it can be used as a solvent for many different polymers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mixtures of existing solvents, such as FA and AA with chloroform, acetone, N, N-dimethylformamide, dichloromethane, or even hexafluoro-2-propanol, have been used until now for nano- or micro-fibrous mats preparation by electrospinning [ 57 , 58 , 63 ]. Virgin polyamide has already been electrospun for many applications, such as water or air filtration, composites with antioxidant activity, or improved mechanical properties [ 53 , 54 , 55 , 56 ]. HFIP is an acidic alcohol, and due to its strong hydrogen bonding properties, it can be used as a solvent for many different polymers.…”
Section: Resultsmentioning
confidence: 99%
“…The antibacterial activity of neat rPA or rPA/MAG fibrous membranes was tested by the standard agar diffusion technique [ 55 ]. The fibrous layers were cut into circular disks (diameter 9 mm).…”
Section: Methodsmentioning
confidence: 99%
“…Staphylococcus aureus is the most commonly occurring bacteria causing infectious diseases. For this purpose, the development of antibacterial clothing is a necessity for the sports industry [112][113][114]. It was reported that the use of chitosan fibers in sportswear and socks delivered the properties like antibacterial, fungicides, and moisture balance [115,121].…”
Section: Use Of Nanotechnology In Sportswear and Shoesmentioning
confidence: 99%
“…These photocatalytic agents could be implanted into sportswear [134]. Nano-sphere™ was produced by a company named Schoeller Textile AG to manufacture self-cleaning fabrics for sports textiles [112]. Self-cleaning properties can be achieved through super-hydrophobic and super-hydrophilic surfaces as shown in Figure 13.…”
Section: Use Of Nanotechnology In Sportswear and Shoesmentioning
confidence: 99%
“…This with the aim to obtain waterproof and breathable textiles [ 17 ]. In the work of Irfan et al [ 18 ], electrospun membranes of polyvinylidene fluoride and polyvinyl pyrrolidone were modified with different amounts of Ag NPs. These membranes showed antimicrobial activity against S. aureus .…”
Section: Introductionmentioning
confidence: 99%